Smoking and Alcohol Consumption Behavior Among Male Senior High School Students - Meilani, Niken; Hariadi, Sunarru Samsi; Haryadi, Fransiskus Trisakti (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Smoking and alcohol consumption behavior prevailed greater among adolescents period. These behavior could cause health risks. About 1 of every 4 adolescents in Indonesia were smokers and 3% of adolescents were drinking alcohol. This study aimed to analyze the association between self-efficacy with smoking and alcohol consumption among adolescents. This was a cross-sectional study carried out in July-September 2022. The study population was high school male students in Yogyakarta. A multistage random sampling technique was employed, involving 163 respondents. The instrument used was a questionnaire that has been tested. Data was analyzed in chi-square. Almost half of males had smoking behavior (39,3%). Males who were smoking started their behavior at the mean age of 15 years old. Most of them had low self-efficacy (70,6%). All male adolescents who had high self-efficacy do not have alcohol drink behavior. There was a relationship between self-efficacy with smoking behavior (p=0,001) and alcohol consumption (p=0,004). Strengthening self-efficacy is essential for adolescents. The government, family, and peers have an important role in increasing self-efficacy